Material quantities and estimated construction costs for new elevated IRC 2015-compliant single-family home foundations - Kodavatiganti, Yamini; Rahim, Md Adilur; Friedland, Carol J.; Mostafiz, Rubayet Bin; Taghinezhad, Arash; Heil, Shandy (Frontiers in Built Environment, 2023)
Residential foundation selection is critical for the lifetime performance of the project, but the type of foundation selected can depend on cost. This study aims to compare the new construction costs of residential slab-on-fill and four types of crawl space foundations for residential projects by quantifying the material quantities for each and exploring the effect of building characteristics on material quantities and total costs. The building characteristics selected are size (139 m2, 186 m2, and 232 m2), footprint aspect ratio (1:1, 1:2.5, and 1:5) and first floor elevation (0 m to 1.2m in 0.3 m increments). We find that material quantities and total costs change not only with building size and elevation, but also with footprint aspect ratio. Applying 2022 RSMeans Building Construction Cost data, the results show that for any building size, aspect ratio, or elevation, raised wood flooring on pier foundations ($118–$180 per m2) and slab on fill ($103–$211 per m2) are the least expensive, while crawl space foundations with stemwalls are the most expensive ($147–$280 per m2). The results of this study can be used by residential builders, developers and designers in evaluating foundation costs and design alternatives. The methodology may also be adapted for use in other applications such as flood mitigation or energy efficiency projects or environmental sustainability assessments.